1997
DOI: 10.1111/j.1432-1033.1997.00792.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding of 1‐Anilinonaphthalene‐8‐Sulfonic Acid to α‐crystallin

Abstract: a-Crystallin was found to exhibit a time-dependent uptake of the hydrophobic probe, l-anilinonaphthalene-8-sulfonic acid (ANS), similar to that typically observed with lipid membranes. Analysis of the interaction of ANS with a-crystallin revealed two types of interactive processes, partitioning and binding. The predominant process involved partitioning, with a coefficient of 300 M-'. The binding component had the following characteristics: 1 binding site124 subunits and a Kd of about 9 pM. The binding was unaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 41 publications
1
13
2
Order By: Relevance
“…These data suggest that hydrophobic forces are dominant in the ANS binding to ␣-crystallin. The fact that ␣A-and ␣B-crystallin have two sets of binding sites is in agreement with the studies of Stevens and Augusteyn, who suggested two kinds of interactions for the binding of ANS to ␣-crystallin (22). Moreover, binding of destabilized mutants of T4 lysozyme to ␣-crystallin was demonstrated to be biphasic (28).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…These data suggest that hydrophobic forces are dominant in the ANS binding to ␣-crystallin. The fact that ␣A-and ␣B-crystallin have two sets of binding sites is in agreement with the studies of Stevens and Augusteyn, who suggested two kinds of interactions for the binding of ANS to ␣-crystallin (22). Moreover, binding of destabilized mutants of T4 lysozyme to ␣-crystallin was demonstrated to be biphasic (28).…”
Section: Resultssupporting
confidence: 90%
“…Historically, hydrophobicity has been measured qualitatively and quantitatively by spectroscopic methods like fluorescence and equilibrium dialysis, mostly by using two common fluorescent dyes, 8-anilino-1-naphthalenesulfonic acid (ANS) and bis-ANS (19,20,22,24). In such cases, indirect methods such as van't Hoff analysis for obtaining thermodynamic parameters to elucidate ANS binding are often limited.…”
mentioning
confidence: 99%
“…The difference in dissociation constants determined by the three methods was not significant. These values are five to eight times lower than the K d value for ANS binding to ␣-crystallin reported recently (39).…”
Section: Discussioncontrasting
confidence: 65%
“…There is, however, disagreement with respect to the number of hydrophobic sites available within ␣-crystallin as determined by the environment-sensitive probe ANS (38,39). We used bis-ANS instead of ANS to determine the nature of hydrophobic sites in ␣-crystallin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation